Ecohydraulic quantification of hydropeaking alterations by the use of hydrosignatures: a two scale approach. Issue 2 (1st April 2017) - Le Coarer, Yann; Testi, Baptiste; Beguin, Jérémy
Abstract : Hydropeaking flow fluctuations can affect aquatic fauna in various ways, depending on the river's morphological characteristics. We have developed a method for quantifying hydropeaking events by drawing up hydrosignatures. In a given flow, a hydrosignature quantifies the hydraulic diversity in any area/part of the aquatic space defined by either volume or area percentages on a depth and current velocity cross grid. When a two-dimensional hydraulic model for hydropeaking events is available, in a given reach, a comparative hydrosignature index can be calculated between the hydrosignature of the present time step and the initial hydrosignature, or between two hydrosignatures separated by a constant time interval. This method is useful to determine where major changes have occurred along a river, and to classify hydropeaking intensities. This approach can be used to analyse the level of hydraulic transformation of an entire reach but does not focus on the sides of the channel inhabited by the juvenile fish, which are particularly exposed to the effects of flow fluctuations. Juvenile habitats can be defined by suitability indexes which are attributed to hydraulic classes of hydrosignatures. The total weighted usable area of a juvenile habitat can be calculated at all the time steps in a hydraulic simulation by partitioning any hydraulic mesh into hydraulic classes. An index quantifying the damage to juvenile populations can then be defined by calculating the maximum change in habitat area observed during the hydropeaking event.